Intermittent Blue Light Supplementation Affected Carbohydrate Accumulation and Sugar Metabolism in Red-Light-Grown Tomato Seedlings - Xiangyu Gao; Lingzhi Li; Wenzhong Guo; Yifan Zhai; Xiaoming Wei; Xiaoli Chen (Horticulturae)
According to previous studies, dynamic light regimes might enhance seedling development, survival rates, or economic efficiency in factory-based seedling production systems compared to continuous red and blue light irradiation. However, there have been few studies revealing the effects of discontinuous red and blue light on the carbohydrate accumulation and metabolism of tomato seedlings. Therefore, we planted tomato seedlings in an artificial light plant factory under a red background light with intermittent blue light intervention, namely R (as the control), R/RB32, R/RB40, R/RB64, and R/RB80 at an equal daily light integral. The growth, carbohydrate accumulation, and sugar metabolism were analyzed to investigate the effects of dynamic lighting modes on tomato seedlings. The results demonstrated the following: (1) Pure red light induced spindling of tomato seedlings, while intermittent blue light treatments enhanced stem thickness, leaf number, and leaf area, resulting in greater biomass accumulation. Among these treatments, the highest antioxidant enzyme activity and the lowest reactive oxygen species (ROS) content, accompanied by the highest biomass, were all observed in tomato seedlings subjected to R/RB80 (intermittent supplementation of 80 μmol·m−2·s−1 blue light under red light background). (2) The carbohydrate accumulation in tomato seedlings was increased under all treatments relative to the control. The sucrose content, enzyme activity, and gene expression level of sucrose phosphate synthase (SPS) were all up-regulated in tomato leaves treated with blue light irradiation compared with pure R. In addition, the highest soluble sugar content, along with the peak SPS activity and gene expression, was observed under the R/RB80 treatment. Meanwhile, the lowest fructose content accompanied by the lowest activity and gene expression of sucrose synthase (SS) were observed in tomato leaves treated with R/RB32. This implies that blue light supplementation may regulate sugar accumulation by modulating the activity or expression of enzymes involved in sucrose metabolism. (3) Moreover, shoot biomass, enzyme activity, and expression level of SPS were all found to increase with the increase in supplementary blue light intensity, indicating that short-duration high-intensity blue light was more effective in promoting carbohydrate accumulation in tomato seedlings than long-term low-intensity blue light based on the equal DLI.